An Investigation of How Financial Attitudes and Experiences Affect Personality-Mediated Management Behavior in MSMEs - Fitriansyah Fitriansyah; Susilo Utomo; Rina Apriliani; Ratnawita Ratnawita; Alfiana Alfiana (International Journal of Economics Development Research (IJEDR), 2024)
In this study, personality-mediated management behavior in MSMEs in Semarang City is examined and tested in relation to financial attitudes and financial experience. Version 25 of SPSS was used to process the data. In Semarang City, 88 MSME business actors made up the sample. The study findings indicate that there is a substantial relationship between personality and financial views as well as experience. There is a considerable impact of financial attitudes on management conduct. Regarding how management conduct is impacted by financial experience. Personality has a major impact on how managers behave. Not only does financial experience have a substantial impact on management behavior mediated by personality, but financial views also have a big influence. Thus, each of the seven current hypotheses has a noteworthy and beneficial impact.